BENTUK TARI MEGATRUH KARYA DARYONO - Mutiara Nabiella; Pramutomo Pramutomo (Institut Seni Indonesia Surakarta, 2019)
The Megatruh dance is one of the traditional dance performed by a single man based on contemporary style, created by Daryono. This is one of the works which is applied Surakarta style (Kasunanan and Mangkunagaran) and Yogyakarta. This work was born from a creativity possessed by Daryono, enriched by many improvised patterns in the performance. Therefore, it can be concluded from this study that the objective of the study was to examine the form and development of creative elements in the Megatruh dance. Studying the problem of the dance’s form used the concept of Alma M. Hawkins which was highlighted by Suzane K. Langer’s thought. Meanwhile, to discuss the problem of developing the creative elements, this study used the concept of Sandra Cerny Minton. The writing process and review of the study used qualitative methods with descriptive analysis models to explain the form. The results of this study was that the form of this work is a structured improvisation carried out directly on the stage. It was totally relied on how Daryono used his body and applied his dance experience on his work, Megatruh Dance. Keywords: Megatruh Dance, Development of Creative Elements, Forms.